Spectroscopic and molecular docking elucidation to binding characteristics of bovine serum albumin with bupropion an aminoketone-medication for nicotine addiction - Makegowda, Manjushree; Doddarevanna, Revanasiddappa Hosakere (European Journal of Chemistry, 2019)
One of the highly soluble protein presents in circulatory system of bovine body is bovine serum albumin (BSA). Bupropion hydrochloride (BRN) served to treat prime smoking cessation and disorder due to depressive. BRN binding to BSA was studied by molecular docking and lots of spectroscopic (UV-vis, emission, synchronous, 3D fluorescence, CD and FT-IR) methods at pH = 7.40. Static quenching with strong binding was obtained for BSA-BRN system by forming complex. Secondary structures, conformations and microenvironments of BSA were altered after BRN interaction. Distance between BRN and BSA was also achieved. Biologically active metal ions (Cu2+, Ca2+, Mg2+, Fe2+ and Zn2+) were also influenced on the BSA-BRN complex. Bonds of hydrogen and Van der Waals were major binding forces to stabilize BSA-BRN complex at site I (IIA) of BSA. Hence, binding of BRN to transport protein (BSA) is of prominent importance and these findings could be helpful for BRN pharmacology and potential clinical research.